On the long run effects of market splitting: Why more price zones might decrease welfare. (July 2016) - Grimm, Veronika; Martin, Alexander; Weibelzahl, Martin; Zöttl, Gregor
Abstract: In liberalized electricity markets we observe different approaches to congestion management. While nodal pricing is implemented in Canada and some markets in the United States, European markets are split up into a limited number of price zones with uniform prices, in order to at least partially realize the benefits of regional price differentiation. Zonal boundaries often coincide with national borders, but some countries are also split into multiple zones. In this paper we shed light on possible negative welfare effects of market splitting that arise in a model where investment incentives in new generation capacity are taken into account if zones are misspecified. We show that standard approaches to configure price zones – on the basis of projected nodal price differences or congested transmission capacity – may fail to suggest reasonable zone specifications. Also an adjustment of Available Transfer Capacities (ATCs) between zones or a switch to flow-based market splitting does not ensure positive welfare effects. Our analysis suggests that a careful and detailed evaluation of the system is needed to ensure a reasonable zone configuration. Abstract : Highlights: We analyze investment and production in energy only markets with market splitting. Market splitting can lead to decreased welfare even for reasonably chosen zones. We identify the reasons for the negative impact of introducing prices zones.